PENDEKATAN PENDIDIKAN BERBASIS MUTU - Ridwan Idris (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2009)
It is widely accepted that educational institution plays an important role in developing human resource. Due to this, high quality educational institutions should be thoroughly developed. It is argued that to develope high quality education depends strongly on the government policy, particularly in the issue of autonomy level of the institution. The concept of school based management which leads educational institution to be more independent is a relevant model of developing good quality education. This model allows community at large to actively participate in developing the quality of education.